2021
DOI: 10.1186/s13098-021-00625-8
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of circ-FANCA alleviates LPS-induced HK2 cell injury via targeting miR-93-5p/OXSR1 axis in septic acute kidney injury

Abstract: Background Sepsis is life-threatening disease with systemic inflammation and can lead to various diseases, including septic acute kidney injury (AKI). Recently, diverse circular RNAs (circRNAs) are considered to be involved in the development of this disease. In this study, we aimed to elucidate the role of circ-FANCA and the potential action mechanism in sepsis-induced AKI. Methods HK2 cells were treated with lipopolysaccharide (LPS) to establish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 40 publications
1
49
0
Order By: Relevance
“…CircRNAs have been demonstrated to compete with mRNAs for miRNAs binding, which inhibit downstream gene expression 30 . The biological functions of circRNA/miRNA/mRNA axis in sepsis have been revealed 31,32 . More importantly, bioinformatics analysis predicted the complementarity between miR‐17‐5p and circTLK1/PARP1.…”
Section: Introductionmentioning
confidence: 99%
“…CircRNAs have been demonstrated to compete with mRNAs for miRNAs binding, which inhibit downstream gene expression 30 . The biological functions of circRNA/miRNA/mRNA axis in sepsis have been revealed 31,32 . More importantly, bioinformatics analysis predicted the complementarity between miR‐17‐5p and circTLK1/PARP1.…”
Section: Introductionmentioning
confidence: 99%
“…OXSR1 is a serine/threonine kinase that regulates downstream kinases in response to environmental stress and is responsible for the co-transportation of ions in kidney [ 47 ]. Previous research revealed that OXSR1 level was higher in the serum of sepsis-related AKI patients compared to healthy individuals, and OXSR1 protein expression was strongly enhanced in LPS-stimulated HK2 cells compared to control cells [ 48 ]. In this study, OXSR1 expression was lifted in LPS-challenged cells and CLP-induced rats, which was in line with previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL10 [76], SIGLEC1 [77] and IL1R2 [78] have been suggested to be associated with neurological diseases. CXCL9 [79], SIGLEC1 [80], IL1R2 [81], KLF15 [82] and CD207 [83] [146], STAT4 [147], CXCL8 [148], KLF2 [149], ADM (adrenomedullin) [150], EGR1 [151], TRIB1 [152], SOD2 [153], OXSR1 [154], IL6R [155], CD44 [156], LRG1 [157], PFKFB2 [158], PACSIN2 [159], MYH9 [160], DOT1L [161], CXCL16 [162], PTEN (phosphatase and tensin homolog) [163], FOXO3 [164], DDIT4 [165], PINK1 [166], IQGAP1 [167], ADIPOR1 [168], MTMR3 [169], USF2 [170], SGK1 [171], GSTO2 [172], ETS2 [173], TKT (transketolase) [174], CMIP (c-Maf inducing protein) [175], THBD (granzyme A) [464], IFNG (interferon gamma) [465], IFIH1 [466], STAT1 [467], CCR5 [468], ADCY5 [469], MT2A [470], DPP4 [471], FASLG (Fas ligand)…”
Section: Discussionmentioning
confidence: 99%